2008
DOI: 10.1021/ac800289f
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Aerodynamic Ionization Source for Remote Analyte Sampling and Mass Spectrometric Analysis

Abstract: The use of aerodynamic devices in ambient ionization source development has become increasingly prevalent in the field of mass spectrometry. In this study, an air ejector has been constructed from inexpensive, commercially available components to incorporate an electrospray ionization emitter within the exhaust jet of the device. This novel aerodynamic device, herein termed remote analyte sampling, transport, and ionization relay (RASTIR) was used to remotely sample neutral species in the ambient and entrain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…However, the application of ambient mass spectrometry is limited by the low collection efficiency and the shortness of the transport distance from the sample to the sampling orifice of the mass spectrometer when the analysis of large or remote sampling substrates is required, especially nonvolatile samples on solid substrates. [20][21][22] It has been shown that techniques such as fused-droplet electrospray ionization (FD-ESI) [23,24] and extractive electrospray ionization (EESI) [25][26][27] transport analytes as neutral molecular species into an ESI plume to facilitate ionization and mass spectrometric detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of ambient mass spectrometry is limited by the low collection efficiency and the shortness of the transport distance from the sample to the sampling orifice of the mass spectrometer when the analysis of large or remote sampling substrates is required, especially nonvolatile samples on solid substrates. [20][21][22] It has been shown that techniques such as fused-droplet electrospray ionization (FD-ESI) [23,24] and extractive electrospray ionization (EESI) [25][26][27] transport analytes as neutral molecular species into an ESI plume to facilitate ionization and mass spectrometric detection.…”
mentioning
confidence: 99%
“…The remote analyte sampling, transport, and ionization relay (RASTIR) source using an air ejector provided a direct means of locally or remotely collecting nonvolatile neutral analytes for subsequent ionization in ESI. [22,28] An extra pumping system was used to provide additional suction to assist in transfer of ions from an LTP ambient ion source to the mass spectrometer. [29] The Vapur TM interface (IonSense Inc., Danvers, MA, USA) using a slow pump coupled with DART collects more of the desorption gas containing ions and transfers it over a shorter distance to the atmospheric pressure ionization (API) orifice region.…”
mentioning
confidence: 99%
“…26) ii) Gas phase/aerosols sampling e sample is vaporized using heater or laser and the thermally desorbed sample vapor or the ablated aerosols, or both, are carried by compressed air ow or suction to the suitable ion source. [27][28][29][30] For volatile sample, APCI or other discharge based ionization is usually the preferred choice, but gaseous ionization with ESI also works. 29) ere are some limitations of these methods to perform practical in-vivo analysis on living animal or human.…”
Section: Remote Ambient Mass Spectrometrymentioning
confidence: 99%
“…The development and implementation of molecular transport devices such as the air amplifier [26,27], air ejector [28], and remote analyte sampling, transport, and ionization relay (RASTIR) [29], which enable the efficient transport of ions into the mass spectrometer have been investigated and may prove important to increasing sensitivity.…”
Section: Maldesi-ltq-ft-icr Of Peptides and Proteinsmentioning
confidence: 99%